(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The approaches to determination the essence of the concept of «social potential of society» are analyzes in the article. On the basis of which the main signs of the social potential of society are identified. The author’s interpretation of the concept are formulated. The scientists approaches to the component structure of social potential of society are considered, on the basis of generalization of that authorial approach is developed. In particular a structure of social potential of society include demographic potential, fertile potential social and infrastructural potential, potential of employment, the potential of social policy, the potential of social solidarity